THE RELATIONSHIP BETWEEN STRESS LEVEL AND MENSTRUAL CYCLE IN STUDENTS AT SMK INSAN MANDIRI AL-KHAIRI, LEBAK REGENCY IN 2023 - Putri T., Hevi Yolanda; Yuliani, Indah (HEARTY, 2025)
Background: Based on a preliminary study conducted at Vocational Secondary School Insan Mandiri Al-Khairi, Lebak Regency, it was found that 80% (16 out of 20) female students experienced menstrual cycle disorders. Purpose: To determine the relationship between stress levels and menstrual cycles in female students at Vocational Secondary School Insan Mandiri Al-Khairi, Lebak Regency. Methods: Cross sectional through a point time approach where samples were taken using a total sampling of 97 respondents. Data analysis using chi square test. Results: Shows stress levels related to the menstrual cycle (p-value 0.001). Conclusion: There is a relationship between stress levels and female students' menstrual cycles. It is hoped that students can strengthen coping mechanisms in dealing with stressors when carrying out their duties as students at school and their adolescent life outside of school so that the menstrual cycle becomes regular and the growth and development process becomes optimal.